Osteoarthritis and falls among older adults / Sumaiyah Mat - Sumaiyah , Mat (2017)
Falls are major public health problem in older adults. Fall-related injuries have been reported as the leading causes of years lived with disability globally. While osteoarthritis, a common degenerative joint disorder, has been considered an established risk factor for falls. Our literature review has found limited evidence and conflicting results to support this assumption. This study was performed and analysed in a two-staged design: 1) a case-control comparison of characteristics related to OA among fallers and non-faller controls, 2) a pre-planned subgroup analysis of individuals with OA within a randomized controlled trial of multifaceted interventions in the secondary prevention of falls in older people. Cases consisted of 229 fallers; individuals aged 65 years and above with a history of two falls or one injurious fall in the past 12 months. 160 control participants were non-fallers, aged 65 and above without no history of falls. Regardless of the definition used, OA was not associated with falls. However, different degrees of severity of OA symptoms in varying OA definitions showed an interesting relationship with falls. In individuals with radiological OA, mild symptoms appear protective of falls which was probably due to increase of anxiety while those with clinical OA and severe symptoms are at increased risk of falls compared to those with mild symptoms mediated by fear of falling. Thus, OA was not directly associated with falls, however, psychological problems secondary to OA might have a different impact on the risk of falls. In a separate study of postural control (n=102), impaired postural balance found among fallers was not influenced by presence of OA. The poorer EPE observed in individuals with symptomatic OA appeared to have a protective effect against falls. An evaluation of the features of OA detected on MRI revealed that that presence of sub-chondral cysts and menisceal tears mediates in increase in postural sway among fallers. iv Among our older participants with OA, fallers had higher serum TIMP2 level, indicating that falls among older adults with OA was associated with a higher degree of degeneration. In the subgroup analysis of individuals with OA from the RCT on multifactorial intervention for falls, the modified Otago exercise improved postural control and reduced fear of falling in those with pre-existing impairments in gait and balance. In essence, this study has contributed to existing knowledge on falls by contradicting previously unsubstantiated assumptions of the association between OA and falls. Instead, a sinusoidal relationship appears to exist between OA and falls, with mild OA being protective of falls and severe OA predisposing to falls. Falls risk appears to be influenced by psychological status, while impaired dynamic postural control associated with increased falls risk is not influenced by the presence of OA. However, the presence of sub-chondral cyst and menisceal tear detected by MRI did mediate the impaired postural control observed in our fallers. In our serological analysis, falls among older adults with OA were associated with a more active degenerative state. The improvement in postural control and falls efficacy observed among our OA fallers, suggest that the modified Otago is potentially benefical, and will serve as a pilot study for a larger randomized-controlled study for secondary falls prevention for individuals with OA.